Implementasi Metode Tabulasi pada Rangkaian Listrik 2 Loop Guna Meningkatkan Hasil Tes dan Respon Siswa - Haniyah Alivia (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
One of the physics materials that is considered difficult is electricity, especially on the subject of closed 2-loop electrical circuits. The students' abilities in solving 2 loop electricity problems still have difficulties in understanding and solving various problems with limited time. The aim of this research is to provide an alternative solution in solving the 2-loop closed electrical circuit problem using the tabulation method and to determine the increase in test results and student responses using the tabulation method. The method in this research uses quantitative research with experimental methods. Analysis of test results uses the N-Gain test while analysis of student responses uses a Likert scale. The results of this research are an increase in test results for 2-loop closed electrical circuits using the tabulation method, namely in the high category with an N-Gain value of 0.89. Meanwhile, students' responses to the use of the tabulation method were categorized as very positive with a percentage of 89.79%. This shows that the tabulation method can be implemented by students in solving 2-loop closed electrical circuit problems.
Reuploud file repositori 29 Jan 2026_Yudi
Keywords: Tabulation Method; Test Results; Student Responses